Implementation of Agricultural Land Protection Policy on The Transfer of Functions And Food Security Efforts in The Special Region of Yogyakarta - Puspitaningrum, Silvia Diah; Mudiparwanto, Wahyu adi (LEGAL BRIEF, 2024)
The shrinking of agricultural land is felt in the Special Region of Yogyakarta, where agricultural land is shrinking, and causing food security in Yogyakarta to be threatened. The efforts made by the government by issuing several policies are felt to have not provided a way. This study aims to provide an overview of the implementation of ineffective regional policies, and food security efforts for Yogyakarta. The data obtained in this study came from news sources, journals, and interviews. The data obtained is classified according to the formulation of the problem, then processed with qualitative descriptive analysis, so that the results are obtained in the form of a systematic review until the final results are obtained in the form of conclusions and suggestions. The approach in this study uses a legislative approach, which is in accordance with the regulations regarding the Agricultural Land Protection Policy. Then the Conceptual approach which refers to the application of legal concepts and law enforcement principles regarding the implementation of agricultural land protection policies. The results of this study show that the implementation of the policy is still ineffective, and other efforts are needed to maintain pagan resilience in Yogyakarta